Recording Classical Music - Toft, Robert (Focal Press, 2019)
Recording Classical Music presents the fundamental principles of digitally recording and editing acoustic music in ambient spaces, focusing on stereo microphone techniques that will help musicians understand how to translate "live" environments into recorded sound. The book covers theory and the technical aspects of recording from sound source to delivery: the nature of soundwaves and their behavior in rooms, microphone types and the techniques of recording in stereo, proximity and phase, file types, tracking and critical listening, loudness, meters, and the post-production processes of EQ, control of dynamic range (compressors, limiters, dynamic EQ, de-essers), and reverberation (both digital reflection simulation and convolution), with some discussion of commercially available digital plugins. The final part of the book applies this knowledge to common recording situations, showcasing not only strategies for recording soloists and small ensembles, along with case studies of several recordings, but also studio techniques that can enhance or replace the capture of performances in ambient spaces, such as close miking and the addition of artificial reverberation. Recording Classical Music provides the tools necessary for anyone interested in classical music production to track, mix, and deliver audio recordings themselves or to supervise the work of others.